Homo stalker, or the Zone as a hunting field (an interpretation of the film by Andrei Tarkovski) - Sobolevska, Olena (Actual Problems of Mind, 2017)
The author interprets a symbolic image of the Zone presented in a film by A. Tarkovsi «Stalker». The main attention is paid to the questions of the relationships between human as a stalker and a hunter on the one side, and the world as a field where one hunts for the true being on the other.